Охотничьи птицы: Труды по охоте / Л. П. Сабанеев ; сост. Е. А. Калганов - Сабанеев Леонид Павлович (Физкультура и спорт, 1989)
Экземпляры: П. Ф. (20210507) / Инвентарный номер: 26000 / Цена: 3.40 / Авт.знак: С 12 / ГРНТИ: 68 / ББК: 47.1